Pengembangan E-Book Teknik Gerak Dasar Atletik Siswa Kelas 5 Sd Negeri 39 Kota Lubuklinggau - Tri Juniarti; Ahmad Gawdy Prananosa; Wawan Syafutra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to develop an E-book of basic athletic movement techniques for 5th-grade students of SD Negeri 39 Lubuklinggau City and to determine the quality of the E-book from the aspects of validity and practicality as having a potential effect. This research is development research that refers to developing a 4-D model. The instruments used to measure the quality of the developed E-book include validation sheets and practicality questionnaires with an average score of . The product of this research is an E-book of basic motion techniques for grade 5 elementary school athletics. The results showed that: (1) linguists were categorized as quite valid with a total of 0.64 media experts in the category